2003
DOI: 10.2337/diacare.26.12.3280
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Sensation in Diabetic Neuropathic Foot With Mechanical Noise

Abstract: OBJECTIVE -Localized low-level mechanical or electrical noise can significantly enhance tactile sensitivity in healthy young subjects and older adults. This phenomenon is termed stochastic resonance (SR). In this study, we examined the effect of SR on vibratory and tactile sensation in patients with moderate to severe diabetic peripheral neuropathy. RESEARCH DESIGN AND METHODS-A total of 20 subjects were included in the study. The vibration perception threshold (VPT) test and the Semmes-Weinstein filament (SWF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 24 publications
2
95
2
Order By: Relevance
“…Some studies have also reported that SR improves visual [9], aural [10] and haptic [11] ability. The SR effect in tactile sensitivity has also been confirmed in feet [12], [13], hands and fingers [14], [15], and improved tactile sensitivity is known to influence the sensorimotor functions of humans [7], [8]. It has further been reported that SR improves balance control in humans [16], [17].…”
Section: Introductionmentioning
confidence: 74%
“…Some studies have also reported that SR improves visual [9], aural [10] and haptic [11] ability. The SR effect in tactile sensitivity has also been confirmed in feet [12], [13], hands and fingers [14], [15], and improved tactile sensitivity is known to influence the sensorimotor functions of humans [7], [8]. It has further been reported that SR improves balance control in humans [16], [17].…”
Section: Introductionmentioning
confidence: 74%
“…Some studies have also reported that SR improves visual [9], aural [10], and haptic [11] ability. The SR effect in tactile sensitivity has also been confirmed in feet [12], [13], hands, and fingers [14], [15], and improved tactile sensitivity is known to influence the sensorimotor functions of humans. It has further been reported that SR improves balance control in humans [16], [17].…”
Section: Introductionmentioning
confidence: 79%
“…Fontana et al 21 was able to show that low frequency whole body vibration improved proprioception in the lumbosacral area, and Khaodhiar et al 22 demonstrated an improvement of tactile perception using SRV. We have not tested pelvic floor proprioception in the current study but this subject will be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%